2022
DOI: 10.1177/11771801221089033
|View full text |Cite
|
Sign up to set email alerts
|

Community-based participatory research with Indigenous youth: a critical review of literature

Abstract: Community-based participatory research has gained traction as an innovative approach to research with underserved communities. Community-based participatory research with Indigenous youth, however, is less common. The purpose of this critical review is to explore the conduct of community-based participatory research with Indigenous youth over the past 20 years. Eighteen studies met inclusion criteria; they were evaluated for their respective use of theory, methodology, and findings. One study was quantitative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Community participation does not have a transparent approach, which leads to a lack of clear goals and objectives, and that success cannot be guaranteed. Since the evaluation process is complex, a lack of accountability among practitioners is created [13]. In addition to taking high costs in terms of money, time, and skills, the participation implementation also depends on the community's attitude.…”
Section: Significance Of Community Participationmentioning
confidence: 99%
“…Community participation does not have a transparent approach, which leads to a lack of clear goals and objectives, and that success cannot be guaranteed. Since the evaluation process is complex, a lack of accountability among practitioners is created [13]. In addition to taking high costs in terms of money, time, and skills, the participation implementation also depends on the community's attitude.…”
Section: Significance Of Community Participationmentioning
confidence: 99%
“…There is increasing interest in the application of quantitative tools to Indigenous research in order to supplement qualitative research. Quantitative social science research within Indigenous ways of knowing and being, as reported by Blackstock (2020) and based on Simpson & Mendenhall (2022), emphasizes the possibility of community-based participatory research.…”
Section: Research Typementioning
confidence: 99%
“…Community members prioritized youth safety in the sequencing of research studies, and adaptations were made to ensure adherence to community guidelines (e.g., having a trusted member of the school community recruit the youth, as typically, a research assistant would recruit to avoid coercion). By adapting protocols to uphold community guidelines and preferences, this study took a community-based research approach that promoted collaboration, community wisdom, and co-ownership of research procedures (58,59). This iterative method to the study process is particularly important when considering the history of exploitative research practices that have led to distrust.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%